Seasonal and host-correlated variation in the susceptibility of rice hispa to Beauveria bassiana in the field - HUZARIKA, L K; PUZARI, K C; SAIKIA, D K (The Indian Journal of Agricultural Sciences, 2013)
A survey conducted during June to October 1990, March to October 1991 and April to July 1992 in rice ecosystems of Assam revealed the virulence of Beauveria bassiana (Bals.) Vuill. on eggs, pupae and adults of rice hispa, Dicladispa armigera (Olivier) (Coleoptera:Chrysornelidae). Infection was more prevalent on egg stage and fluctuated during different months. Susceptibility of hispa to fungal attack was also influenced by host plant. B. bassiana appears to be one of the natural mortality factors of rice hispa.